Error Analysis in Descriptive English Writing among Undergraduates in Hunan City University - Qian, Chen; Nair, Subadrah Madhawa (Contemporary Research in Education and English Language Teaching, 2021)
In this age of globalization, EFL writing skills are essential for Chinese undergraduates, especially in the areas of communication, education and business cooperation. The objective of this study is to study and analyze EFL descriptive writing errors among Chinese undergraduates, according to gender and faculty of study. Descriptive research design was employed in this study. The undergraduate students in the study were given a descriptive writing test and their essays were marked by a lecturer using rubric provided by the researchers. The sample of the study consisted of 400 Chinese undergraduate students (200 males and 200 females,) from Hunan City University in Hunan Province, China. Stratified random sampling was employed in selecting the samples. Students’ errors in EFL writing were analyzed based on Corder’s error analysis and James’s classification of errors. The findings from quantitative data revealed that male students made significantly more errors than female students in their overall writing, mechanical, coherence and cohesion, grammar, lexical and sentence structures. There is also significant difference in the mean errors among students from the four faculties. Moreover, the results indicated that the students from the faculties of Education Management and Chinese Language Studies (social sciences) performed better than the students from the other faculties. In terms of pedagogical implications, the findings suggest that further research should be carried out to minimize male students’ errors in their writing skills as well as the students from the Information Technology and Civil Engineering faculties.